Pelan pengurusan taman laut: Pulau Babi Besar, Kepulauan Lima dan Kepulauan Mertang, Mersing Johor - Kassim, Zaleha; Yusof, Zeenat Begam; Zakariya, Khalilah; Ahmad, Zuhairi; Abu Samah, Mohd Armi; Muhamed, Juliana; Ahmad, Ismail (2018)
Marine parks are categorized as a marine protected area (MPA). IUCN (1994) defined MPA as an area of land and/or sea especially dedicated to the protection of biological diversity, and of natural and associated cultural resources, and managed through legal or other effective means. Based on this definition, marine parks management could be a mixed approach of different management objectives as stated under IUCN (1994) and it is not only under the category of IV where the protected area is managed mainly for the sustainable use of natural ecosystem (Managed Resource Protected Area).Management of marine parks should involved not only the responsible agency for the governance, but at the same time involve all stakeholders. It should be run for conservation, also with social and economic objectives, set up for scientific, economic and cultural reason and at the same time value the cultural importance (wilderness), and of course the restoration and rehabilitation (Lee & Julie, 2003).